Efek Variasi Beban Pendinginan Terhadap Coefficient Of Performance (Cop) Alat Uji Pengukuran Koefisien Evaporasi Menggunakan Refrigeran R-134A - Tito Hadji Agung Santosa; Muhammad Nadjib; Thoharuddin Thoharuddin; Muhammad Akhid Riza (Semesta Teknika, 2017)
Investigation of the cooling load effect toward Coefficient of Performance (COP) is important to conduct. The Coefficient of Performance (COP) is related with compressor work and refrigeration capacity in order to produce a refrigeration system which have a high COP. The high COP value can be reached with minimum compressor work, however it has a maximum refrigeration capacity. This research is to know the effect of cooling load variation toward the performance of experimental device of evaporation heat transfer measurement. By knowing the changing of performance toward cooling load variation, it can be useful in design of an effective and efficient air conditioning system.The method of coolecting data is by experimental method that is by varying water mass flowrate (cooling load) which is flowed to evaporator. An evaporator is soak in a 30 xm x 15 cm x 20 cm water box. Water flowrate can be varied and be masured by a water rotameter. Refrigerant is using Freon R-134a. Experiment is conducted with an evaporation heat transfer coefficient device. The device is a model of modified refrigeration system by adding instruments : an orifice, a test section, and an electric heater. Thermocouple and some pressure gauges is installed at some points which has been determined. Thermocouple and pressure gauges is used to collect temperature and pressure data. After conducting an experiment by evaporator cooling load variation, temperature and pressure data is got. Furthermore based on the temperature and pressure data, the enthalpy is got and can be used to counting the compressor power. Refrigeration capacity can be counted from total heat absorbed by evaporator from water and is divided refrigerant mass flowrate. In this research is got results that cooling load given in evaporator enfluences the COP of the experiment device. By increasing in cooling load at the determined variation, the Coefficient of Performance (COP) of the device is increase. In this research it get results increasing of COP at some refrigerant mass flowrate. The maximum result is get at minimum range inverter variation, that is 16 Hz (ṁr = 9,4 g/s - 10,26 g/s) and the maximum cooling load variation is 2 LPM with COP of 4,96. Whereas the minimum results is get at the maximum inverter range variation, that is 24 Hz (ṁr = 11,83 g/s - 12,25 g/s) and the minimum cooling load variation is 1 LPM with COP of 1,98. This research give some information, if a cooling load of an air conditioning room is chanhing, then it will change the parameter (temperature and pressure) and COP of the air conditioning system in a room.